Bongkar pasang kurikulum indonesia: dampak kebijakan pergantian kurikulum terhadap proses pembelajaran - Fisabilillah, Dita (Maliki Interdisciplinary Journal, 2025)
As time progressed, the curriculum in Indonesia underwent 12 changes. This article discusses the impact of the curriculum change policy in Indonesia on the learning process. This research was motivated by complaints felt by education stakeholders regarding curriculum changes. Using library methods to analyze the positive and negative impacts of curriculum changes. The results of the analysis show that changes can improve the quality of education and also complement the shortcomings of the previous curriculum. This article recommends the need for socialization regarding curriculum renewal, provision of adequate resources, and parental involvement in the educational process to support the achievement of new curriculum goals.